2017
DOI: 10.1111/tmi.12939
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of 6‐min walk test with left ventricular function and quality of life in heart failure due to Chagas disease

Abstract: The distance walked during the 6MWT correlates with BNP, quality of life and parameters of left ventricular diastolic function in ChD patients with heart failure. We propose this test to be adopted in endemic areas with limited resources to aid in the identification of patients who need referral for tertiary centres for further evaluation and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…In the present study, risk factors for the prognosis of PIH complicated with heart failure were also analyzed. The results showed that blood pressure, 6MWT, LVEF and LVEDD were independent risk factors for the disease, consistent with the views of Chambela et al (27).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, risk factors for the prognosis of PIH complicated with heart failure were also analyzed. The results showed that blood pressure, 6MWT, LVEF and LVEDD were independent risk factors for the disease, consistent with the views of Chambela et al (27).…”
Section: Discussionsupporting
confidence: 90%
“…The 6MWD has been used as part of several assessment parameters including physical function, exercise capacity, quality of life, and a prognostic marker of readmission or mortality. 32,33) Oxygen uptake, which is regulated by cardiac function and skeletal muscle function, is a standard marker of exercise capacity. 8) In patients with heart failure, 6MWD and oxygen uptake are shown to be correlated, and 6MWD can be used as a prognostic marker of heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…One of the preplanned outcomes (6‐min walk test) was not obtainable from all patients at all time points due to technical reasons. The results obtained for 6‐min walk test at baseline evaluation were previously published …”
Section: Methodsmentioning
confidence: 99%